Low accuracy and confidence in chest radiograph interpretation amongst junior doctors and medical students. Issue 7 (8th July 2018) - Cheung, Timothy; Harianto, Harry; Spanger, Manfred; Young, Alan; Wadhwa, Vikas
Abstract: Accurate chest X‐ray (CXR) interpretation is an essential skill in clinical practice. Previous studies have shown poor accuracy and confidence rates (CR) of CXR interpretation by junior doctors and medical students. We presented 10 chest radiographs via an online questionnaire to Australian medical students and junior doctors, who were asked to identify the radiographic abnormality from a list of 15 options and to rate their confidence for each answer. Of 67 complete responses, junior doctors achieved a mean score of 57.6% and medical students 56.1%, with CR of 67 versus 58% respectively. There was a significant positive relationship between accuracy and CR among junior doctors (Pearson's coefficient + 0.798, P = 0.006) and students (Pearson's coefficient + 0.716, P = 0.020). This study identified similarities in strength and weakness in CXR interpretation between medical students and junior doctors. There was a positive association between test scores and self‐rated confidence scores.